A new focus on... the British Empire, c.1500-present KS3 history - Allen, Tom; Barma, Salma; Durbin, Ed (A new focus on..., 2023)
It's time to tell the story of the Empire from the perspectives of peoples who were colonised. Understand the nuances of the British Empire in different periods and places as you examine this complex, controversial history with respect and rigour. > Explore differing experiences around the world. This book has more breadth and depth than any other, helping pupils to consider what the Empire meant for people in Ireland, America, the Caribbean, India, China, Australia, New Zealand, Africa, Iraq, Palestine and Britain, across a period of over 500 years. > Look at the Empire like a real historian. Influenced by recent historical scholarship, we give agency to the indigenous people of the colonies and tell their stories for the first time in a school textbook. By focusing on consequences or experiences and asking better questions, we move far away from the traditional balance sheet approach. > Diversify your KS3 curriculum. Designed to be used flexibly, the book contains short enquiries that can be slotted into any schemes of work that you follow. Structured into three key periods, it empowers you to teach the Empire in a way that suits you and your pupils, whether that's chronologically, geographically or thematically. > Benefit from the insight of 11 authors. Our diverse author team comes from across the UK, bringing a richness of perspectives and lived experiences to the narrative. Together, they have a shared commitment to changing and improving what pupils learn about the Empire. > Trust the academic seal of approval. The authors have worked with 25 historians from the very start of the project, who have reviewed the content to ensure that the historiography is accurate and up to date. --- A NEW FOCUS ON... The textbooks that belong in your classroom. The people and stories that belong in your curriculum. Look at topics through a